Evaluación de material particulado pm 10 y pm 2,5 en la parroquia Machachi cantón Mejía para generar un mapeo de comparación de calidad de aire en zonas afectadas. - Carrera Tello, Estefany Marcela (2024)
In air pollution, suspended particles, also known as Particulate Matter (PM), are the most common pollutants present in the atmosphere.Therefore, this research analyses PM 10 and PM 2.5 in the parish of Machachi, in the canton of Mejía. The monitoring of particulate matter was carried out at four points located in accessible places with high and low vehicular flow, using E-BAM equipment that allowed sampling during 24 hours. The methodology used was based on the interpolation of geostatistical analysis, the validation and selection of the estimation model for each hour of monitoring and the application of map algebra, using the ArcGIS geographic information system. Two interpolation methods were applied in this software: IDW and ordinary Kriging, obtaining PM10 and PM 2.5 values for the entire study area. The PM10 particulate matter concentration data does not exceed the maximum permissible limit (100 3⁄ in a 24-hour average) according to Regulation 097-A , obtaining as average concentration of point one 143⁄, the second point 163⁄, the third point 11 3⁄ and the last point is 10 3⁄. As for the values obtained from the monitoring of PM 2. 5 it was determined that they do not exceed the maximum permissible limit (50 3⁄ in a 24-hour average) according to Regulation 097-A, being defined for point one 12 3⁄ and in the second point 133⁄ the third sample point is from 123⁄ and the last point is from 93⁄. It was determined that the interpolation method that best fits to PM10 is KRIGING - Spherical, otherwise in PM2.5 the interpolation method that best fits is IDW.Mitigation measures include the following alternatives: urban vegetation, carshing, particulate matter monitoring plan, among others.